The Influence of Learning Outcomes in Digital Image Prosesing and the Experience of Industrial Technical Internship toward Students’ Entrepreneurship Interest in XI Multimedia Class at SMK Negeri 8 Semarang - Ashri, Haningtiyas Nur Shalati; Widodo, Antonius Tri; Raharjo, Tri Joko (Universitas Negeri Semarang, 2018)
The role of vocational school is very important in realizing the nation’s autonomy by becoming an entrepreneur. This research was done for analyzing: (1) the relationship between learning result of Digital Image Prosesing towards students’ entrepreneurship interest. (2) The relationship between Industrial Technical Internship experiences toward students’ entrepreneurship interest. (3) The relationship between the Digital Image Prosesing and the Industrial Technical Internship experiences toward student's entrepreneurship interest. (4) the effect of learning outcomes in Digital Image Prosesing and Industrial Technical Internship experience toward student's entrepreneurship interest. (5) How are the effects of Digital Image Prosesing and Industrial Technical Internship experiences toward student's student interest. This research is a descriptive associative study which used quantitative method. Results of the Research: (1) There is a significant and positive relationship between the learning outcomes of Digital Image Prosesing toward the students' entrepreneurship interest that is equal to 0.330. (2) There is a significant and positive relationship between the Industrial Technical Internship experiences toward the student's entrepreneurship interest that is 0.445. (3) There is a significant and positive relationship between the learning outcomes of Digital Image Prosesing and Industrial Technical Internship experience toward student's entrepreneurship interest that is 0.624. (4) Students’ understanding as the learning outcomes of Digital Image Prosesing and Industrial Technical Internship experiences have positive effects toward students’ entrepreneurship interest that is equal to 38.9%. (5) Based on table in summary model it is obtained the probability value (sig.F change) = 0.000. Because the value of sig.F change 0.000 < 0.05 then the decision is H0 rejected and Ha accepted. This result means that PRAKERIN (Industrial Technical Internship) experience and learning outcomes of Citra Digital Image Prosesing are simultaneously and significantly related toward students’ entrepreneurship interest. The benefits for education field, the implementation of learning Digital Image Prosesing and Industrial Technical Internship in developing entrepreneurial interest can be a reference and innovation for students, enable the graduated students to have high interest in entrepreneurship